2018
DOI: 10.4049/immunohorizons.1800048
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Binding Groove Contraction Linked to the Lack of T Cell Response: Using Complex Structure and Energy To Identify Neoantigens

Abstract: Using personalized peptide vaccines (PPVs) to target tumor-specific nonself-antigens (neoantigens) is a promising approach to cancer treatment. However, the development of PPVs is hindered by the challenge of identifying tumor-specific neoantigens, in part because current in silico methods for identifying such neoantigens have limited effectiveness. In this article, we report the results of molecular dynamics simulations of 12 oligopeptides bound with an HLA, revealing a previously unrecognized association bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Other approaches to model peptides in class I MHC binding grooves have incorporated docking, molecular dynamics simulations, protein threading, or combinations of these methods. These other methods have reported Cα or full-atom RMSD values between model and experiment within the approximate range of 1–2 Å (8, 16, 37, 4350). Our approach thus compares favorably with or even outperforms other efforts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches to model peptides in class I MHC binding grooves have incorporated docking, molecular dynamics simulations, protein threading, or combinations of these methods. These other methods have reported Cα or full-atom RMSD values between model and experiment within the approximate range of 1–2 Å (8, 16, 37, 4350). Our approach thus compares favorably with or even outperforms other efforts.…”
Section: Resultsmentioning
confidence: 99%
“…Yet for a peptide bound to an MHC protein, the impact of features such as exposed hydrophobic surface and charges are determined by the peptide's conformation within the binding groove, as well as the size and position of the various amino acid side chains. Thus, efforts to predict peptide immunogenicity should be strengthened by approaches that account for the structural properties of peptide/MHC complexes (8, 16, 35).…”
Section: Introductionmentioning
confidence: 99%
“…To complement existing NGS-based methods for neoantigen identification, various studies have investigated additional quantifiable measures to improve neo-epitope prediction scoring. Novel methods described include peptidome analysis [32,51,52], differentiation from self-antigens [53,54], similarity to viral or bacterial antigens [54,55], RNA expression [51,56], and spatial variation in antigen recognition [57,58]. Additionally, novel advances in the knowledge of neoantigen mechanisms has also indicated that methodologies may have to be even more varied in the future to account for factors other than what is traditionally considered for the peptides [59,60].…”
Section: Variations On Traditional Identification and Selection Methodsmentioning
confidence: 99%
“…In fact, one study found that mutated anchor residues on epitopes are conservative, and including this knowledge in a prediction algorithm contributed to increased accuracy in neoantigen identification [61]. Additionally, an atom-based method has been used to assess the propensity of the HLA-peptide complex to bind with TCR based on conformational changes that happen after the HLA-peptide association [58].…”
Section: Variations On Traditional Identification and Selection Methodsmentioning
confidence: 99%
“…However, physics-based and structure-based models can provide a rational background to these findings: for instance, the energetic gain of burying a hydrophobic residue by complex formation strongly depends on the 3D structural features. Given these premises, considering structural aspects alongside sequence holds the promise of giving better prediction of peptide immunogenicity and TCRs binding specificities. …”
Section: Antigen and Epitope Discoverymentioning
confidence: 99%